Catalytic properties of supported Mo2C synthesized by microwave irradiation in hydrazine hydrate decomposition reaction - A. M. Aghoyan; R. A. Mnatsakanyan; D. H. Davtyan (ՀՀ ԳԱԱ հրատ.)
Microwave-assisted synthesis and catalytic processes of Mo2C/carrier systems have been studied. Catalytic tests were carried out on hydrous hydrazine decomposition reaction. Supported Mo2C has shown catalytic activity in decomposition reaction. The catalytic activity changes depending on the carrier’s characteristics. The highest catalytic activity is observed in the reaction with Mo2C/iy-Al2O3 system (95.4%). In all cases decomposition of hydrazine was 100% selective with respect to ammonia and nitrogen. Իրականացվել է Mo2C/կրիչ համակարգերի սինթեզը միկրոալիքային եղանակով և դրանց կատալիտիկ հատկությունների ուսումնասիրությունը՝ միկրոալիքային վառարանում: Կատալիտիկ փորձարկումները իրականացվել են հիդրազինհիդրատի քայքայման ռեակցիայում: Mo2C/կրիչ համակարգերը ցուցաբերում են կատալիտիկ ակտիվություն քայքայման ռեակցիայում և կախված կիրառված կրիչի հատկություններից համակարգի կատալիտիկ ակտիվությունը փոփոխվում է: Ամենաբարձր կատալիտիկ ակտիվությունը դիտվել է Mo2C/iy-Al2O3 /հիդրազին ռեակցայիում (95.4%): Բոլոր դեպքերում հիդրազինի քայքայումն ընթացել է 100% ընտողականությամբ՝ ամոնիակի և ազոտի առաջացմամբ: Изучены микроволновый синтез и каталитические процессы систем Mo2C / носитель. Каталитические испытания были проведены по реакции разложения гидразинагидрата. Mo2C на носителе показал каталитическую активность в реакции разложения. В зависимости от характеристик носителя она изменяется. Наи-большая каталитическая активность наблюдается при реакции с системой Mo2C/iy-Al2O3 (95.4%). Во всех случаях разложение гидразина было на 100% селективным по отношению к аммиаку и азоту.
Keywords: Physical Chemistry